Kinetic Study of Pyrolysis Characteristics of Coal from Inner Mongolia Region - Zhou, Quan; Zhang*, Yongfeng; Chen, Xiangyun; Min Zhang, Yin (Asian Journal of Chemistry, 2014)
Pyrolysis characteristics of different coals from Inner Mongolia region in China were analyzed by TGA technology under non-isothermal condition with a heating rate of 10 °C/min from room temperature to 980 °C in a nitrogen atmosphere. The maximum pyrolysis rate and characteristic peak temperatures were determined by TG-DTG technology. Thermogravimetric data at low and high temperature were analyzed respectively by the reaction rate model assuming the first-order kinetics and the third-order model F3. Apparent activation energy and frequency factor of pyrolysis reaction of coal from Inner Mongolia region were estimated by Coast-Redfern integral method. The results showed that pyrolysis of coal from Inner Mongolia region at the low temperature have the characteristics of the lower value of mass loss, the larger apparent activation energy and frequency factor compared with that at the high temperature.